Human Trial for the Effect of Plasma-Activated Water Spray on Vaginal Cleaning in Patients with Bacterial Vaginosis - Jang, Yongwoo; Bok, Junsoo; Ahn, Dong Keun; Kim, Chang Koo; Kang, Ju Seop (Medical sciences, 2022)
Underwater plasma discharge temporally produces several reactive radicals and/or free chlorine molecules in water, which is responsible for antimicrobial activity. Hence, it can simply sanitize tap water without disinfectant treatment. Additionally, the spraying technique using cleaning water exploits deep application in the narrow and curved vaginal tract of patients. Herein, we attempted a clinical trial to evaluate the vaginal cleaning effect of spraying plasma-activated water (PAW) to patients with vaginitis (46 patients). The efficacy was compared with treatment with betadine antiseptics used to treat bacterial vaginosis (40 patients). To evaluate the cleaning effect, Gram staining of the vaginal secretions was conducted before and after spraying PAW or betadine treatment (BT). Consequently, PAW-sprayed (PAWS) patients (22.3%) showed a better vaginal cleaning effect against Gram-positive and -negative bacteria than BT patients (14.4%). Moreover, 18 patients in the BT group showed worsened vaginal contamination, whereas five patients in the PAWS group showed worsened vaginal contamination. Taken together, the noncontact method of spraying cleaning water to the vagina exhibited a reliable vaginal cleaning effect without further bacterial infection compared with BT. Therefore, we suggest a clinical application of the spraying method using PAW for vaginal cleaning to patients with vaginitis without disinfectants and antibiotics.
Keywords: Female; Humans; Povidone-Iodine; Vagina; Vaginitis; Vaginosis, Bacterial; Water; bacterial vaginosis; plasma-activated water; underwater plasma discharge; vaginal cleaning